DGI-042 Hypomagnesemia as a Possible Marker of Efficacy in Patients with Head and Neck Carcinoma in First-Line Treatment with Cetuximab. (12th March 2013) - Ruiz, J; Megías, JE; Borrell, C; Marrero, P; López, E; Poveda, JL
Abstract : Background: It has been reported that the determination of magnesium levels could be used as a surrogate marker of efficacy in chemotherapy regimens with cetuximab. Purpose: To investigate the hypomagnesemia caused by cetuximab as a predictor of efficacy and outcome in patients affected by head and neck cancer in first-line treatment. Materials and Methods: Retrospective observational study (Study period: November 2008–October 2012). We analysed patients with head and neck carcinoma treated with cetuximab in first-line treatment, who had magnesium determinations from the start of treatment until one month after the end of treatment with cetuximab. Patients with magnesium determinations were stratified into two groups: Patients who presented hypomagnesemia during the treatment (<1.7 mg/dL) and patients who didn't present hypomagnesemia. The primary outcome was to compare remission rate, progression-free survival (PFS) and overall survival (OS) in the two groups. PFS and OS were both determined by the Kaplan-Meier product-limit method. Results: We collected a total of 14 patients (92.8% male). The median age at onset of treatment was 61 years (range: 21–86). Six patients developed hypomagnesemia during treatment. The most common diagnosis was carcinoma of the oral cavity (28.6%) followed by laryngeal carcinoma (21.4%). The group of patients who presented hypomagnesemia showed a higher remission rate (66.7% vs. 37.5% patients), OS [mean: 34.8 (18.8 to 50.9)) vs. 22.4 (95% CI: 11.9 to 32.9 months, p = 0.532] and PFS [34.5 months (18.11 to 50.9), vs. 19.7 (7.8–31.5) p = 0.456] in comparison with the group in which hypomagnesaemia was not detected. Conclusions: Despite the small number of patients studied, hypomagnesemia could be a marker of cetuximab efficacy in first-line treatment in patients with head and neck cancer. Magnesium levels should be determined routinely in patients treated with cetuximab. No conflict of interest.